High-fluidity ceramic particle reinforced copper-based composite powder and preparation method thereof
By premixing and acoustic resonance treatment of low spherical copper powder with ceramic particles, a high-flowability ceramic particle-reinforced copper-based composite powder was prepared, which solved the problem of ceramic particles falling off and achieved efficient copper powder 3D printing.
Patent Information
- Application Number
- CN202411501925.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
AI Technical Summary
In current copper powder 3D printing, the mixing uniformity between ceramic particles and copper powder is difficult to achieve, resulting in the fall of ceramic particles and causing the problem of parts cracking.
Using the original copper powder with low spherical shape and reinforced phase ceramic particles, premixed through a V-shaped mixer, followed by multi-stage mixing treatment in the acoustic resonance equipment, and finally high flowability is prepared in the plasma spherical powder making equipment. Ceramic particle-reinforced copper-based composite powder.
The spherical shape and fluidity of the composite powder are significantly improved, the problem of ceramic particles falling off is avoided, and the printing quality and efficiency are improved.
Smart Images

Figure CN119433278A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials and additive manufacturing, and relates to a high-fluidity ceramic particle reinforced copper-based composite powder and a preparation method thereof. Background Art
[0002] Copper plays a key role in many industries due to its excellent electrical and thermal conductivity and corrosion resistance, especially in the electrical, electronic, aerospace, automotive and medical fields. The copper powder 3D printing market has shown significant growth in recent years and has gradually become an important branch of additive manufacturing (AM). 3D printing technology can not only produce complex geometric structures, but also realize customized production, which greatly expands its market space. Copper powder 3D printing is particularly suitable for the production of small batches, complex shapes or high-performance parts that are difficult to manufacture by traditional methods.
[0003] The development of copper powder 3D printing technology is closely related to additive manufacturing technologies such as powder bed fusion (PBF) and directed energy deposition (DED). PBF technology selectively melts metal powder through laser or electron beam, and forms parts layer by layer. Its advantage is that it can produce complex geometric shapes and is suitable for small and medium-sized and high-precision parts. DED directly melts and deposits metal materials by arc or laser, which is suitable for manufacturing large structural parts. The gradual maturity of these technologies has enabled copper powder 3D printing to have higher precision and better mechanical properties. From the perspective of market application, copper powder 3D printing has shown a wide range of application potential. In the electronics industry, copper powder 3D printing has been used to manufacture parts such as inductors, radiators, antennas and high-frequency connectors. Traditional manufacturing methods are difficult to produce complex geometric structures, while 3D printing can meet the needs of miniaturization and complex design by precisely controlling the deposition of materials, and improve the functionality and design flexibility of electronic components. In addition, copper powder 3D printing also shows great development potential in the fields of aerospace and automotive manufacturing. Lightweight and high-performance parts such as efficient heat exchangers, turbine blades, fuel nozzles, etc. can be produced through copper powder 3D printing technology, which not only reduces manufacturing costs but also improves the performance of parts.
[0004] However, the current copper powder 3D printing market is also facing challenges brought by the high reflectivity and thermal conductivity of the material. Currently, more than 99% of metal 3D printing equipment on the market uses red laser as a heat source, which makes it difficult for copper powder to be melted and formed more effectively, resulting in difficulties in improving printing quality and efficiency. By compounding micro-nano ceramic particles on the surface of copper powder, the printability of copper powder can be effectively improved. However, it is very difficult to mix micro-nano ceramic particles with copper powder evenly. For example, methods such as ball milling and ultrasonic method can only achieve relative uniformity. In recent years, acoustic resonance technology has shown strong adaptability in this field. Its principle for mixing powders is based on the physical properties of acoustic resonance, especially the vibration and resonance phenomenon generated when sound waves propagate in the medium. This technology can evenly mix powders of different materials through the resonance effect of sound waves, especially for powders with large density differences or different physical properties. The mixing uniformity and output of this technology are improved compared with other methods. However, in the process of mixing ceramic particles and copper powder, the ceramic particles still have the problem of easy falling off after the mixing powder treatment using acoustic resonance technology, which often leads to local stress concentration caused by the agglomeration of ceramic particles after falling off from the copper powder during the printing process, thereby causing parts to crack. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a high-fluidity ceramic particle reinforced copper-based composite powder and a preparation method thereof, which can utilize low-sphericity original copper powder and reinforced phase ceramic particles to prepare copper-based composite powder with high sphericity, and greatly improve the powder fluidity of the composite powder to solve the problems raised by the background technology.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A high-fluidity ceramic particle reinforced copper-based composite powder, wherein the raw material mass fraction ratio of the high-fluidity ceramic particle reinforced copper-based composite powder is as follows: copper powder for additive manufacturing accounts for 97-99.5%, and reinforcing phase ceramic particles account for 0.5-3%.
[0008] Furthermore, the copper powder for additive manufacturing includes pure Cu, CuZn 10 、CuCrZr、CuZn 30 、CuZn 36 、CuZn 37 , CuSn4, CuSn6 and CuSn8 or a combination of more.
[0009] Furthermore, the reinforcing phase ceramic particles include one or more combinations of carbides and borides.
[0010] Furthermore, the average particle size of the copper powder for additive manufacturing is 15-55 μm, the average particle size of the reinforcing phase ceramic particles is 20-800 nm, and the copper powder for additive manufacturing is nearly spherical or irregular in shape, and the reinforcing phase ceramic particles are irregular in shape.
[0011] A method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder, which is used to prepare the high-fluidity ceramic particle reinforced copper-based composite powder, specifically comprises the following steps:
[0012] Step 1. Powder premixing: copper powder for additive manufacturing and reinforced ceramic particles are premixed through a V-type mixer to obtain a uniform powder;
[0013] Step 2. Multi-stage mixing of powders: transferring the uniform powder to an acoustic resonance device and performing a multi-stage mixing process through the acoustic resonance device to obtain a uniformly mixed powder;
[0014] Step 3. Plasma spheroidization: The uniformly mixed powder is loaded into a plasma spheroidization powder making device for processing to obtain a high-fluidity ceramic particle reinforced copper-based composite powder.
[0015] Furthermore, in step 1, the mixing speed of the V-type mixer is 50 rpm-400 rpm, and the mixing time is 0.5-8 h, so as to perform homogenous mixing pretreatment on the reinforcement phase ceramic particles and the copper powder for additive manufacturing.
[0016] Further, in step 2, the multi-stage mixing process includes a primary mixing process and a secondary mixing process performed sequentially.
[0017] Furthermore, the frequency of the primary mixing treatment is 80-90 Hz, the acceleration is 40-100g, the mixing time is 1-10 minutes, and the water cooling supply of the acoustic resonance equipment is interrupted; the purpose of this is to break the agglomeration of fine powders and improve the mixing uniformity of the composite powder; unlike the common acoustic resonance technology that maintains the frequency at 60 Hz vibration frequency, the purpose of setting the vibration frequency to 80-90 Hz is that the internal temperature generated by the acoustic resonance equipment in the high frequency state will continue to rise, and the internal pressure of the mixing container will continue to rise due to the temperature rise without water cooling, thereby prompting the composite powder movement state to reach the state of maintaining the optimal mixing acceleration faster, thereby effectively reducing the probability of nanoparticle agglomeration.
[0018] The frequency of the secondary mixing treatment is 60 Hz, the acceleration is 40-100 g, the mixing time is 5 min-60 min, and the water cooling supply of the acoustic resonance equipment is reopened; the purpose is to mix the composite powder at a better vibration frequency for a long time, so that the ceramic particles can be evenly coated on the surface of the copper powder.
[0019] Furthermore, the plasma spheroidization powder making equipment is a DC arc plasma spheroidization powder making equipment.
[0020] Furthermore, the process parameters of the DC arc plasma spheroidization powder making equipment are: power of 10-80kW, powder feeding speed of 0.1-2.0kg / h, and gas consumption of 100-1000L / h.
[0021] The beneficial effects of the present invention are:
[0022] The present invention solves the problem of ceramic particles falling off after mixing treatment of ceramic particle reinforced copper-based composite powder, thereby avoiding the problem of local stress concentration caused by agglomeration of ceramic particles after falling off during printing, which in turn causes cracking of parts. The ceramic particle reinforced copper-based composite powder prepared by the present invention has a sphericity and fluidity close to those of high-sphericity copper powder prepared by mature processes on the market, and the fluidity of the high-fluidity ceramic particle reinforced copper-based composite powder obtained in a Hall flow velocity test is close to that of the high-sphericity copper powder, and is significantly higher than the copper-based composite powder prepared by the traditional high-energy ball milling method.
[0023] Secondly, the copper powder raw material (copper powder for additive manufacturing) used in the present invention is low-sphericity copper powder (nearly spherical or irregular shape), which has low requirements on the production process control of the copper powder and can usually be produced by water atomization, which can effectively reduce costs.
[0024] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0026] Figure 1 The scanning electron micrograph of the original copper powder with low sphericity;
[0027] Figure 2 Scanning electron micrograph of the copper-based composite powder reinforced with high sphericity and high fluidity ceramic particles after the plasma spheroidization step.
[0028] Figure 3 The Hall flow rate test comparison results of the high-sphericity and high-flowability ceramic particle reinforced copper-based composite powder prepared by the present invention, common pure copper powder on the market, and copper-based composite powder prepared by traditional high-energy ball milling method are shown. DETAILED DESCRIPTION
[0029] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0030] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0031] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0032] See also Figure 1-2 It is a high-fluidity ceramic particle reinforced copper-based composite powder. The mass fraction ratio of its raw materials is: copper powder for additive manufacturing accounts for 97-99.5%, and reinforcing phase ceramic particles account for 0.5-3%.
[0033] Wherein, the copper powder for additive manufacturing includes pure Cu, CuZn 10 、CuCrZr、CuZn 30 、CuZn 36 、CuZn 37 , CuSn4, CuSn6 and CuSn8 and other copper alloys; the reinforcing phase ceramic particles include at least one of carbides (TiC, B4C, WC, etc.) and borides (TiB2, TiB, ZrB, etc.).
[0034] Specifically, the average particle size of the copper powder for additive manufacturing is 15-55 μm, the average particle size of the reinforcing phase ceramic particles is 20-800 nm, and the copper powder is nearly spherical or irregular in shape, and the reinforcing phase ceramic particles are irregular in shape.
[0035] This embodiment also provides a method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder, which uses low-sphericity copper powder and reinforced ceramic particles to prepare a copper-based composite powder with high sphericity, and greatly improves the powder fluidity of the copper-based composite powder, specifically comprising the following steps:
[0036] Step 1: Premix the low-sphericity copper powder and the reinforcement phase ceramic particles through a V-type mixer to make them macro-uniformly mixed to obtain macro-uniform powder;
[0037] Step 2: The macroscopic uniform powder obtained in step 1 is loaded into an acoustic resonance device, and subjected to high-frequency mixing and medium-frequency mixing respectively so that the reinforcing phase ceramic particles are evenly coated on the surface of the copper powder to obtain a mixed uniform powder;
[0038] Step 3: The uniformly mixed powder obtained in step 2 is loaded into a plasma spheroidization powder making device to prepare a high-fluidity ceramic particle reinforced copper-based composite powder with high sphericity.
[0039] Specifically, in step 1, the raw material mass fraction ratio of the macroscopic uniform powder is: pure copper powder for additive manufacturing accounts for 97% (copper powder with low sphericity), and reinforced phase WC ceramic particles (reinforced phase ceramic particles) account for 3%. The scanning electron micrograph of the pure copper powder with low sphericity is as follows: Figure 1 shown.
[0040] Furthermore, in step 1, the average particle size of the pure copper powder is 32-36 μm, and the average particle size of the reinforcement phase WC ceramic particles is 50-200 nm.
[0041] Furthermore, in step 1, the pure copper powder is nearly spherical or irregular in shape, and the reinforcing phase WC ceramic particles are irregular in shape.
[0042] Furthermore, in step 1, the composite powder is pre-mixed using a V-type mixer, with a mixing speed of 400 rpm and a mixing time of 0.5-8 h.
[0043] Furthermore, in step 2, the powder mixing process parameters in the acoustic resonance device are: under a high-purity inert gas atmosphere, the high vibration frequency is 90 Hz, the acceleration is 60 g, and the mixing time is 10 min; the medium frequency is 60 Hz, the acceleration is 80 g, and the mixing time is 60 min.
[0044] Further, in step 3, the plasma spheroidization powder making equipment is a DC arc plasma spheroidization powder making equipment, and the plasma spheroidization process parameters are: power of 40kW, powder feeding speed of 2kg / h, gas consumption of 1000L / h, and the scanning electron micrograph of the high sphericity and high fluidity ceramic particle reinforced copper-based composite powder after the plasma spheroidization step is as shown in Figure 2 shown.
[0045] like Figure 3 As shown, the fluidity of the high-sphericity and high-fluidity ceramic particles reinforced copper-based composite powder in the Hall flow rate test is close to the fluidity of the common high-sphericity pure copper metal powder on the market, and is significantly higher than the copper-based composite powder prepared by traditional high-energy ball milling.
[0046] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A high-fluidity ceramic particle reinforced copper-based composite powder, characterized in that: The raw material mass fraction ratio of the high-fluidity ceramic particle reinforced copper-based composite powder is as follows: copper powder for additive manufacturing accounts for 97-99.5%, and reinforcing phase ceramic particles account for 0.5-3%.
2. The high-fluidity ceramic particle reinforced copper-based composite powder according to claim 1, characterized in that: The copper powder for additive manufacturing includes pure Cu, CuZn 10 、CuCrZr、CuZn 30 、CuZn 36 、CuZn 37 , CuSn4, CuSn6 and CuSn8 or a combination of more.
3. The high-fluidity ceramic particle reinforced copper-based composite powder according to claim 1, characterized in that: The reinforcement phase ceramic particles include one or a combination of carbides and borides.
4. The high-fluidity ceramic particle reinforced copper-based composite powder according to claim 1, characterized in that: The average particle size of the copper powder for additive manufacturing is 15-55 μm, the average particle size of the reinforced phase ceramic particles is 20-800 nm, and the copper powder for additive manufacturing is nearly spherical or irregular in shape, and the reinforced phase ceramic particles are irregular in shape.
5. A method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder, characterized in that: The method for preparing the high-fluidity ceramic particle reinforced copper-based composite powder described in any one of claims 1 to 4 specifically comprises the following steps: Step 1. Powder premixing: copper powder for additive manufacturing and reinforced ceramic particles are premixed through a V-type mixer to obtain a uniform powder; Step 2. Multi-stage mixing of powders: transferring the uniform powder to an acoustic resonance device and performing a multi-stage mixing process through the acoustic resonance device to obtain a uniformly mixed powder; Step 3. Plasma spheroidization: The uniformly mixed powder is loaded into a plasma spheroidization powder making device for processing to obtain a high-fluidity ceramic particle reinforced copper-based composite powder.
6. The method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder according to claim 5, characterized in that: In step 1, the mixing speed of the V-type mixer is 50 rpm-400 rpm, and the mixing time is 0.5-8 h.
7. The method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder according to claim 5, characterized in that: In step 2, the multi-stage mixing process includes a primary mixing process and a secondary mixing process performed in sequence.
8. The method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder according to claim 7, characterized in that: The frequency of the primary mixing process is 80-90 Hz, the acceleration is 40-100 g, the mixing time is 1-10 min, and the water cooling supply of the acoustic resonance device is interrupted; The frequency of the secondary mixing process is 60 Hz, the acceleration is 40-100 g, and the mixing time is 5 min-60 min.
9. The method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder according to claim 5, characterized in that: The plasma spheroidization powder making equipment is a DC arc plasma spheroidization powder making equipment.
10. The method for preparing a high-fluidity ceramic particle reinforced copper-based composite powder according to claim 9, characterized in that: The process parameters of the DC arc plasma spheroidizing powder making equipment are: power of 10-80kW, powder feeding speed of 0.1-2.0kg / h, and gas consumption of 100-1000L / h.